Audit Committee Characteristics and Audit Report Lag - Sultana, Nigar; Singh, Harj; Van der Zahn, J-L.W. (Wiley-Blackwell, 2015)
This study seeks to determine whether audit committee compositional features are associated with the timeliness of financial reporting by Australian firms. Timeliness of financial reporting by firms, of which the length of an audit is a fundamental component, adds information content and impacts firm value, making an examination of audit report lag determinants important. Results indicate that audit committee members with financial expertise, prior audit committee experience and those who are independent are associated with shorter audit report lag. Results suggest that legislation mandating audit committee financial expertise and independence are effective also in improving the timeliness of financial reporting. More importantly, our results suggest that there may be benefits in constituting audit committees with other compositional features such as prior committee experience in overall efforts to improve the timeliness, and therefore quality, of financial reporting by firms.